Three-dimensional porous copper foil for battery current collector and preparation method of three-dimensional porous copper foil

Through chemical etching and electrochemical treatment technology of nitric acid, three-dimensional porous copper foils with suitable pore volume, pore size and thickness were prepared, which solved the problem of uneven deposition of lithium metal in lithium-ion batteries by traditional two-dimensional copper foils, significantly improving the electrochemical performance and cycle stability of the battery.

CN119725558APending Publication Date: 2025-03-28TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411705373.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to structural limitations in traditional two-dimensional planar copper foils in lithium-ion batteries, the deposition of lithium metal is uneven and prone to falling off, affecting battery performance and safety.

Method used

Copper nitrate is generated by chemical etching of nitric acid, then heat treatment is carried out to convert it into copper oxide, and then electrochemical treatment is performed in an alkaline etching solution to promote the growth of nanoneedle arrays, form a three-dimensional porous structure, and double-sided nanocubic oxide porous copper foil is generated through secondary heat treatment.

Benefits of technology

It significantly improves the electrochemical performance and cyclic stability of lithium-ion batteries, provides more lithium metal deposition sites, inhibits the growth of lithium dendrites, and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154399260000131
    Figure BDA0005154399260000131
  • Figure BDA0005154399260000141
    Figure BDA0005154399260000141
  • Figure BDA0005154399260000142
    Figure BDA0005154399260000142
Patent Text Reader

Abstract

The invention provides a three-dimensional porous copper foil for a battery current collector and a preparation method of the three-dimensional porous copper foil. The method comprises the following steps: performing chemical etching on a copper foil through a dilute nitric acid solution to generate copper nitrate; carrying out first heat treatment on the copper oxide to convert the copper oxide into copper oxide; the structural stability of the copper foil can be enhanced, and active sites can be provided to promote the formation of a three-dimensional porous structure during subsequent electrochemical treatment; then, a uniform and stable pore structure is successfully constructed on the surface and the interior of the copper foil through alkaline solution electrochemical etching and secondary heat treatment; and the three-dimensional porous copper foil with proper pore volume, pore diameter and thickness is generated. Therefore, the charging and discharging efficiency and the cycling stability of the battery are remarkably improved. In addition, the preparation method is simple, easy to control and beneficial to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper foil preparation, and in particular relates to a three-dimensional porous copper foil for battery current collector and a preparation method thereof. Background Art

[0002] As an efficient and environmentally friendly energy storage device, lithium-ion batteries play a vital role in modern technology and daily life. With the rapid development of electric vehicles, portable electronic devices, and renewable energy storage systems, the performance requirements for lithium-ion batteries are getting higher and higher. In order to meet these demands, the innovation and optimization of battery materials have become a research hotspot. Among them, the current collector is a key component of the battery, and its performance directly affects the overall performance of the battery.

[0003] The current collector is a conductive material used to collect and transfer electrons in lithium-ion batteries. It has an important influence on the electrochemical performance, cycle stability and safety of the battery. In lithium-ion batteries, the current collector is divided into positive current collector and negative current collector, which are used for electron transfer of positive and negative electrode materials respectively. Copper foil is widely used as a negative current collector material due to its excellent conductivity, ductility and chemical stability. However, with the development of lithium-ion battery technology, the traditional two-dimensional planar copper foil current collector can no longer meet the needs of high-performance batteries.

[0004] During the operation of lithium-ion batteries, copper foil acts as a current collector, and lithium metal is deposited on its surface. Since the two-dimensional planar structure of copper foil limits the deposition space of lithium, when too much lithium metal is deposited, due to the lack of sufficient storage space, the lithium metal accumulated on the surface of copper foil will easily fall off due to the poor bonding force between the copper foil and the copper foil. This shedding will not only lead to a decrease in battery performance, but also shorten the battery's cycle life and may cause safety issues.

[0005] To solve this problem, researchers began to explore transforming the two-dimensional planar structure of copper foil into a three-dimensional structure to increase its surface area, thereby providing more lithium metal deposition sites. The emergence of three-dimensional porous copper foil makes it possible to deposit lithium metal uniformly, which helps to inhibit the growth of lithium dendrites, thereby improving battery performance and safety.

[0006] In the existing technology, there are two main methods for converting the planar structure of copper foil into a three-dimensional structure: structural modification and chemical modification. Structural modification usually uses a template method to prepare porous copper foil. Although this method can produce porous copper foil with a specific structure, the process is complicated and costly, and the template is easily worn out. The dealloying method can also be used, but its operation is complicated and the conditions are harsh, which may lead to waste of resources and the purity of the porous copper foil obtained is not high. More importantly, the copper-based material has a poor affinity for metallic lithium, and the three-dimensional porous copper foil is prone to uneven deposition, which can cause dendrite growth and cause safety hazards.

[0007] In contrast, electrochemical etching is a lower-cost method that rapidly grows copper hydroxide or copper oxide nanoneedle arrays on the surface of copper foil through electrochemical reactions to form a porous structure, thereby increasing its surface area and providing more deposition sites for lithium metal. However, the traditional electrochemical etching method still has some problems. For example, the copper foil is only in contact with the etching solution on one side, which makes the operation difficult; or the prepared three-dimensional porous copper foil cannot form fiber bundles or the diameter of the formed fiber bundles is large and uneven, the pore volume is too small, the pore size is too small or too large, resulting in too few porous structures, low strength of the three-dimensional porous structure itself, and even too low strength of the copper foil; or the process conditions such as the concentration and liquid level depth of the composite etching solution are extremely high, which is not conducive to continuous and stable production.

[0008] Therefore, how to simply, quickly, continuously and stably prepare three-dimensional porous copper foil with appropriate pore volume, pore size and thickness has become an urgent problem to be solved in the lithium battery industry. Summary of the invention

[0009] In view of the problems in the prior art, the present invention discloses a three-dimensional porous copper foil for battery current collector and a preparation method thereof. The present invention first performs nitric acid chemical etching on the copper foil to generate copper nitrate, and then performs a first heat treatment on the copper foil to convert it into copper oxide, which is beneficial to maintaining the structural stability of the copper foil. Then, through electrochemical treatment with an alkaline solution, using copper oxide as a starting point, the growth of a nanoneedle array is promoted to form a three-dimensional porous structure. Finally, the porous copper foil is subjected to a secondary heat treatment to convert it into a porous copper foil with double-sided nano copper oxide, thereby generating a stable three-dimensional porous copper foil with suitable pore volume, pore size and thickness; thereby significantly improving the electrochemical performance of the battery. In addition, the preparation method of the present invention is simple and easy to control, which is conducive to industrial production.

[0010] The present invention is achieved through the following technical solutions:

[0011] In the first aspect, the present invention provides a three-dimensional porous copper foil for battery current collector; the nanofiber skeleton diameter of the three-dimensional porous copper foil is 0.1-3 μm, and the pore volume is 0.005-0.03 cm 3 / cm 2 The average pore size is 1-5μm and the thickness of the porous structure is 1-10μm.

[0012] As a further solution, the pore size of the three-dimensional porous copper foil is distributed in the range of 0.05-20 μm.

[0013] In a second aspect, the present invention provides a method for preparing a three-dimensional porous copper foil for a battery current collector according to the first aspect, the preparation method comprising the following steps:

[0014] S1: heating the copper foil in a dilute nitric acid solution for chemical etching to obtain a copper foil containing copper nitrate;

[0015] S2: subjecting the copper foil containing copper nitrate in S1 to a first heat treatment to obtain a copper foil containing copper oxide;

[0016] S3: electrochemically treating the copper foil containing copper oxide in S2 in an alkaline etching solution to obtain a porous copper foil containing nano copper hydroxide and / or nano copper oxide;

[0017] S4: subjecting the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3 to a second heat treatment to obtain a porous copper foil containing nano copper oxide.

[0018] As a further solution, the concentration of the dilute nitric acid solution in S1 is selected from 1-6 mol / L.

[0019] Furthermore, the concentration of the dilute nitric acid solution in S1 is preferably 3-5 mol / L.

[0020] As a further solution, the etching temperature in S1 is selected from 50-100° C., and the etching time is selected from 15-65 s;

[0021] Furthermore, the etching temperature in S1 is preferably from 50 to 80°C.

[0022] As a further solution, in S1, both sides of the copper foil contain copper nitrate; the proportion of copper nitrate is selected from 1%-5%.

[0023] As a further solution, the first heat treatment temperature in S2 is selected from 200-300° C., and the first heat treatment time is selected from 5-120 s.

[0024] Furthermore, the first heat treatment time in S2 is preferably 20-60s, and the heat treatment temperature is preferably 220-280°C.

[0025] As a further solution, the etching solution in S3 includes a strong alkaline solution and ammonia water; the concentration of the strong alkaline solution is selected from 2-5 mol / L; the molar mass ratio of the strong alkaline solution to ammonia water is selected from (2-5): (0.1-1).

[0026] As a further embodiment, the strong alkaline solution is selected from one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and barium hydroxide.

[0027] As a further solution, the electrochemical treatment temperature in S3 is selected from 40-110°C, the electrochemical treatment time is selected from 10-65s, and the current density of the electrochemical treatment is selected from 10-110mA / cm 2 .

[0028] Furthermore, the electrochemical treatment temperature in S3 is preferably 40-65°C, the electrochemical treatment time is preferably 20-30s, and the current density of the electrochemical treatment is preferably 30-60mA / cm 2 .

[0029] As a further solution, the S3 step performs electrochemical treatment in an etching tank; the etching tank is preferably a U-shaped etching tank; the U-shaped etching tank includes a cathode roller and an anode tank; the anode tank is also provided with a by-product collection tank on the side opposite to the cathode roller.

[0030] Furthermore, the anode tank is selected from one or more of a stainless steel anode tank, a lead alloy anode tank, and a titanium-based metal oxide coating anode tank; the cathode roller is selected from one or more of a titanium roller, a nickel roller, a stainless steel roller, and a tungsten roller. As some specific examples: the metal oxide coating is selected from one or more of SnO2, PbO2, Sb2O5, RuO2, IrO2, and MnO2.

[0031] As a further solution, the temperature of the second heat treatment in S4 is selected from 200-450° C., and the time of the second heat treatment is selected from 10-120 s.

[0032] Furthermore, the temperature of the second heat treatment in S4 is preferably 250-350° C., and the time of the second heat treatment is preferably 20-60 s.

[0033] As a further solution, the heat treatment in S2 and S4 may use one or more equipments including an oven, a vacuum heat treatment furnace, and a muffle furnace.

[0034] As a further solution, the copper foil also has a pretreatment step before S1 chemical etching; the pretreatment step is to sequentially subject the copper foil to degreasing with a degreasing liquid, pickling, and water washing.

[0035] As a further embodiment, the degreasing liquid is selected from one or more of petroleum ether, acetone, glycerol, ethanol, n-butanol, and isopropanol;

[0036] As a further solution, the pickling is performed by one or more acid solutions selected from hydrochloric acid, sulfuric acid, acetic acid, and phosphoric acid; the concentration of the acid solution is selected from 20-60wt.%; and the pickling time is selected from 60-200s.

[0037] As a further solution, there is a step S31 between S3 and S4: cleaning the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3; and removing the residual etching solution in S3.

[0038] As a further solution, in step S31, the pH value of the cleaning solution after cleaning is selected from 6-7; the cleaning time is selected from 60-200s; and the cleaning solvent is selected from one or more of water and ethanol.

[0039] In a third aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; wherein the positive electrode sheet and / or the negative electrode sheet comprises the three-dimensional porous copper foil described in the first aspect.

[0040] The characteristics and beneficial effects of the present invention are:

[0041] The three-dimensional porous copper foil modified by three-dimensional porous copper oxide of the present invention has the advantages of lithium affinity, electrolyte wettability, guiding lithium uniform nucleation deposition growth, forming an SEI layer with excellent mechanical properties and stabilizing long battery cycles.

[0042] The present invention firstly treats the copper foil with nitric acid for preliminary etching to generate copper nitrate; then forms an appropriate amount of copper oxide layer on both sides of the copper foil through the first heat treatment. This not only changes the surface morphology of the copper foil, increases the active sites, and provides a good reaction basis for subsequent electrochemical treatment; it also improves the corrosion resistance and stability of the copper foil and reduces the impact of side reactions. Compared with direct high-temperature oxidation to generate copper oxide, this method is simpler and faster and will not damage the copper foil structure.

[0043] Secondly, by placing the copper foil containing copper oxide in an alkaline etching solution for electrochemical treatment, copper oxide is used as the etching starting point to promote the dissolution of copper oxide to form pores, promote the growth of nanoneedle arrays, and form a three-dimensional porous structure; while the undissolved copper oxide keeps the copper foil stable, which is convenient for industrial production. In the present invention, high-temperature heating during the first heat treatment is not only conducive to the conversion of copper nitrate, but also conducive to volatilizing the nitric acid solution remaining on the surface of the copper foil; avoiding uneven etching due to inconsistent local etching solution concentration during subsequent electrochemical etching.

[0044] Finally, a secondary heat treatment is performed to generate a porous copper foil with double-sided nano-copper oxide; the porous copper foil has a suitable pore volume, pore size and thickness; and significantly improves the charge and discharge efficiency and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0046] Figure 1 It is a process flow chart of the method for preparing three-dimensional porous copper foil of the present invention;

[0047] Figure 2 It is a schematic diagram of the structure of a U-shaped etching groove.

[0048] Reference numerals:

[0049] 1- copper foil; 2- cathode roller; 3- anode tank; 4- by-product collection tank. DETAILED DESCRIPTION

[0050] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, and embodiments of the present invention are given, but the scope of the present invention is not limited thereby.

[0051] In the first aspect, the present invention provides a three-dimensional porous copper foil for battery current collector; the nanofiber skeleton diameter of the three-dimensional porous copper foil is 0.1-3 μm, and the pore volume is 0.005-0.03 cm 3 / cm 2 The average pore size is 1-5 μm, and the thickness of the porous structure is 1-10 μm. The nanofiber skeleton refers to the skeleton structure that constitutes the porous structure of the three-dimensional porous copper foil.

[0052] The three-dimensional porous copper foil obtained by the present invention can achieve reasonable fiber bundle diameter, pore volume, pore size distribution, and porous structure thickness while maintaining tensile strength and elongation to the maximum extent; at the same time, they synergistically affect each other to improve electrochemical performance and cycle stability during battery charge and discharge cycles.

[0053] As a further solution, the pore size of the three-dimensional porous copper foil is distributed in the range of 0.05-20 μm.

[0054] In a second aspect, the present invention provides a method for preparing a three-dimensional porous copper foil for a battery current collector according to the first aspect; the preparation method comprises the following steps:

[0055] S1: heating the copper foil in a dilute nitric acid solution for chemical etching to obtain a copper foil containing copper nitrate;

[0056] S2: subjecting the copper foil containing copper nitrate in S1 to a first heat treatment to obtain a copper foil containing copper oxide;

[0057] S3: electrochemically treating the copper foil containing copper oxide in S2 in an alkaline etching solution to obtain a porous copper foil containing nano copper hydroxide and / or nano copper oxide;

[0058] S4: subjecting the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3 to a second heat treatment to obtain a porous copper foil containing nano copper oxide.

[0059] The present invention firstly performs nitric acid heat treatment on the copper foil to achieve preliminary etching, and generates an appropriate amount of copper nitrate on its surface; then, a layer of copper oxide is formed on both sides of the copper foil by heating and decomposing through simple heat treatment; not only the surface morphology of the copper foil is changed, more active sites are formed, and favorable conditions are provided for the growth of nano copper hydroxide or nano copper oxide in the electrochemical etching process; the corrosion resistance and stability of the copper foil are further enhanced, and the influence of side reactions is reduced; and a good reaction basis is provided for subsequent electrochemical treatment. Moreover, compared with directly performing high-temperature oxidation on the surface of the copper foil to generate copper oxide, this method has the advantages of being simple and fast, and can also avoid damage to the copper foil structure.

[0060] Secondly, the present invention places the copper foil containing copper oxide in an etching tank filled with etching solution for further electrochemical treatment. Since the copper foil surface contains an appropriate amount of copper oxide, it can be used as the starting point of electrochemical etching to further adjust the etching. At the same time, it ensures that the remaining copper elements on the copper foil surface are completely grown into a nano needle array structure, thereby forming a three-dimensional porous structure. In addition, through the electrochemical reaction, a part of the copper oxide contained on the copper foil surface gradually dissolves to form tiny pores; these pores can be used as channels for subsequent etching reactions, allowing the etchant to penetrate deeper into the copper foil, thereby forming a more suitable pore size; promoting the rapid growth of nano copper hydroxide and / or nano copper oxide nano needle arrays, forming a three-dimensional porous structure. The undissolved part of the copper oxide maintains the stability of the copper foil structure during electrochemical etching. At the same time, by adjusting the parameters of the electrochemical etching to accurately control the size of the pores, it is conducive to the realization of industrial production.

[0061] Finally, the porous copper foil containing nano copper hydroxide and / or nano copper oxide is subjected to a second heat treatment to transform it into a porous copper foil with nano copper oxide on both sides. This step further stabilizes the porous structure, not only significantly increases the surface area of ​​the copper foil, but also provides abundant sites for the uniform deposition of lithium metal, which helps to improve the conductivity and chemical stability of lithium-ion batteries; and its three-dimensional porous shape can further inhibit the growth of lithium dendrites, providing a strong guarantee for its application in lithium-ion batteries.

[0062] As a further solution, the concentration of the dilute nitric acid solution in S1 is selected from 1-6 mol / L; the appropriate concentration of the dilute nitric acid solution is crucial to the initial etching effect of the copper foil. Too low a concentration may result in insufficient etching and failure to form a sufficient copper nitrate layer; while too high a concentration may result in excessive etching and damage to the integrity of the copper foil. Therefore, the present invention sets the concentration range of the dilute nitric acid solution to between 1-6 mol / L to ensure that an appropriate amount of copper nitrate layer is formed on the surface of the copper foil, laying a good foundation for subsequent electrochemical treatment.

[0063] Furthermore, the concentration of the dilute nitric acid solution in S1 is preferably 3-5 mol / L.

[0064] As a further solution, the etching temperature in S1 is selected from 50-100° C., and the etching time is selected from 15-65 s.

[0065] When etching copper foil with dilute nitric acid, the etching temperature and time are also very important. If the etching temperature is too low, the reaction rate may be too slow and the etching effect is poor; if the temperature is too high, the reaction may be accelerated, resulting in increased surface roughness of the copper foil and even damage to its structure. Therefore, the present invention sets the etching temperature range between 50-100°C to ensure that etching is performed at a reasonable temperature to maintain the integrity of the copper foil. The etching time has a synergistic correlation and needs to be adjusted accordingly according to the growth of the copper foil to achieve the best etching effect.

[0066] Furthermore, the etching temperature in S1 is preferably from 50 to 80°C.

[0067] As a further solution, in S1, copper nitrate is contained on both sides of the copper foil; the proportion of copper nitrate is selected from 1%-5%. An appropriate range of copper nitrate proportion on the surface of the copper foil is conducive to forming a uniform etching effect, ensuring that the reaction activity on both sides of the copper foil is consistent. Too low a proportion of copper nitrate may lead to uneven etching, while too high a proportion may cause excessive etching on the surface of the copper foil, affecting the performance of the final product. Therefore, the present invention, by controlling the proportion of copper nitrate content in an appropriate range, is conducive to forming an appropriate amount of copper oxide to promote subsequent electrochemical etching growth, forming a uniform and dense pore structure, and facilitating obtaining a suitable pore size range; it is also conducive to maintaining the stability of the copper foil structure, avoiding excessive etching and causing damage to the copper foil in subsequent processing.

[0068] As a further solution, the first heat treatment temperature in S2 is selected from 200-300°C, and the first heat treatment time is selected from 5-120s. When the copper foil containing copper nitrate on both sides is heat-treated and heated to decompose into copper oxide, by controlling the temperature and time of the heat treatment, it can be ensured that the copper nitrate is completely converted into copper oxide, while avoiding excessive heat treatment time and excessively high heating temperature that may cause the thickening of the oxide layer on the surface of the copper foil and the increase of the grain size, thereby causing deformation or damage to the copper foil and affecting the performance of the copper foil. It provides a good premise for the subsequent preparation of a three-dimensional porous copper foil with a suitable pore size, pore volume and nanofiber skeleton diameter.

[0069] Furthermore, the first heat treatment time in S2 is preferably 20-60s, and the heat treatment temperature is preferably 220-280°C.

[0070] As a further solution, the etching solution in S3 includes a strong alkali solution and ammonia water; the concentration of the strong alkali solution is selected from 2-5 mol / L; the molar concentration ratio of the strong alkali solution to the ammonia water is selected from (2-5): (0.1-1). When the copper foil containing copper oxide is further electrochemically etched, in order to grow a uniform nano-needle array of nano copper hydroxide and / or nano copper oxide, the present invention uses an etching solution containing a strong alkali solution and ammonia water. The strong alkali solution is used as the main etchant, and its concentration range is set between 2-5 mol / L to ensure that it can effectively react with the copper oxide on the surface of the copper foil during the electrochemical etching process to form the desired nanostructure. The addition of ammonia water plays a role in adjusting the pH of the etching solution, further promoting the etching reaction. At the same time, the present invention also optimizes the etching effect by precisely controlling the molar concentration ratio of the strong alkali solution to the ammonia water within the range of (2-5): (0.1-1), ensuring that the formed nanostructure is uniform and stable.

[0071] As a further embodiment, the strong alkaline solution is selected from one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and barium hydroxide.

[0072] As a further solution, the electrochemical treatment temperature in S3 is selected from 40-110°C, the electrochemical treatment time is selected from 10-65s, and the current density of the electrochemical treatment is selected from 10-110mA / cm 2 . During the electrochemical treatment, the parameters such as the temperature, time and current density of the electrochemical treatment have a comprehensive influence on the formation of the nanostructure. Too low a treatment temperature or too short a treatment time may result in a slow reaction rate and inability to fully etch the copper foil containing copper oxide; while too high a temperature or too long a time may accelerate the reaction and cause damage to the surface structure of the copper foil. In addition, the choice of current density is also crucial, which directly affects the electrochemical etching rate and the formation of the nanostructure. At 10-110mA / cm 2 Within the current density range, the electrochemical etching process can be ensured to be stable, while avoiding the problem of over-etching or under-etching the copper foil surface.

[0073] Furthermore, the electrochemical treatment temperature in S3 is preferably 40-65°C, the electrochemical treatment time is preferably 20-30s, and the current density of the electrochemical treatment is preferably 30-60mA / cm 2 . By further optimizing the parameters of the electrochemical etching treatment, it is helpful to regulate the soluble copper oxide to further form suitable pores, fully forming pore parameters of suitable size on the surface and inside of the copper foil, so as to accommodate more lithium ions and promote uniform deposition; it can also keep some undissolved copper oxide on the surface of the copper foil to maintain the structural integrity of the copper foil. This helps to prepare a three-dimensional porous copper foil with suitable pore volume, pore size, nanofiber skeleton diameter and uniform thickness.

[0074] As a further solution, the S3 step performs electrochemical treatment in an etching tank; the etching tank is preferably a U-shaped etching tank; the U-shaped etching tank includes a cathode roller 2 and an anode tank 3; the anode tank 3 is also provided with a by-product collection tank 4 on the side opposite to the cathode roller 2.

[0075] The design of the U-shaped etching groove 3 enables the by-products generated during the electrochemical etching process to be smoothly collected in the by-product collecting groove 4, thereby preventing the by-products from being deposited on the surface of the copper foil and affecting the etching effect. This design not only improves the etching efficiency, but also ensures the purity of the etching products, providing convenience for subsequent processing. In addition, the U-shaped anode groove 3 also makes the electrochemical contact surface larger and the distance between the cathode and anode consistent, which is conducive to uniform current distribution, thereby ensuring the uniformity and consistency of etching. In addition, the design of the U-shaped etching groove is also convenient for monitoring and adjusting the etching process, improving the stability and controllability of the process.

[0076] Further, the anode tank 3 is selected from one or more of a stainless steel anode tank, a lead alloy anode tank, and a titanium-based metal oxide coating anode tank; the cathode roller 2 is selected from one or more of a titanium roller, a nickel roller, a stainless steel roller, and a tungsten roller. As some specific examples: the metal oxide coating is selected from one or more of SnO2, PbO2, Sb2O5, RuO2, IrO2, and MnO2.

[0077] As a further solution, the temperature of the second heat treatment in S4 is selected from 200-450° C., and the time of the second heat treatment is selected from 10-120 s.

[0078] When a porous copper foil containing nano copper hydroxide and / or nano copper oxide on both sides is subjected to a second heat treatment to obtain a porous copper foil with nano copper oxide on both sides, it is beneficial to completely convert nano copper hydroxide into nano copper oxide by regulating the temperature and time of the second heat treatment, while maintaining the pore structure of the porous copper foil and the integrity of the nanofibers. Too low a temperature or too short a time may lead to incomplete conversion of nano copper hydroxide, affecting subsequent performance; while too high a temperature or too long a time may destroy the pore structure of the copper foil, causing the collapse or merging of the pores, thereby reducing the pore size and pore volume. In addition, too high a temperature may also cause the agglomeration of copper oxide particles, thereby affecting its dispersibility and specific surface area; and the excessive increase in the temperature and time of the second heat treatment promotes the diffusion and rearrangement of substances, resulting in the coarsening of nanofibers. Therefore, it is necessary to select a suitable temperature and time for the second heat treatment to ensure that nano copper hydroxide is completely converted into nano copper oxide, while maintaining the pore structure of the porous copper foil and the stability of the nanofibers.

[0079] Furthermore, the temperature of the second heat treatment in S4 is preferably 250-350° C., and the time of the second heat treatment is preferably 20-60 s.

[0080] As a further solution, the heat treatment in S2 and S4 may use one or more equipments including an oven, a vacuum heat treatment furnace, and a muffle furnace.

[0081] As a further solution, the copper foil also has a pretreatment step before S1 chemical etching; the pretreatment step is to sequentially subject the copper foil to degreasing with a degreasing liquid, pickling, and water washing.

[0082] When the pretreated copper foil is etched and modified into a copper foil with a three-dimensional porous structure, grease, oxides and other impurities on the surface of the copper foil can be removed, improving the purity and surface quality of the copper foil. Such a pretreatment step provides a better base for the subsequent etching and heat treatment process, helping to form a more uniform and stable three-dimensional porous copper foil.

[0083] As a further embodiment, the degreasing liquid is selected from one or more of petroleum ether, acetone, glycerol, ethanol, n-butanol, and isopropanol;

[0084] As a further solution, the pickling is performed by one or more acid solutions selected from hydrochloric acid, sulfuric acid, acetic acid, and phosphoric acid; the concentration of the acid solution is selected from 20-60wt.%; and the pickling time is selected from 60-200s.

[0085] As a further solution, there is a step S31 between S3 and S4: cleaning the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3; removing the residual etching solution in S3. After cleaning the residual etching solution in S3 and then performing a second heat treatment, it is beneficial to promote the copper foil surface to be cleaner and smoother, and form a more uniform and dense nanostructure in the subsequent second heat treatment process, thereby promoting the uniform deposition of lithium ions in the subsequent battery charging and discharging process and inhibiting the growth of lithium dendrites.

[0086] As a further solution, in step S31, the pH value of the cleaning solution after cleaning is selected from 6-7; the cleaning time is selected from 60-200s; and the cleaning solvent is selected from one or more of water and ethanol.

[0087] In a third aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; wherein the positive electrode sheet and / or the negative electrode sheet comprises the three-dimensional porous copper foil described in the first aspect.

[0088] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0089] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0090] Example 1

[0091] (1) Copper foil pretreatment:

[0092] Immerse a copper foil with a thickness of 8 μm in an ethanol solution with a concentration of 30 wt.%, and ultrasonically treat it at 25±5°C for 60 seconds; filter the copper foil, rinse it with ethanol three times, and then dry it; then transfer the dried copper foil to a hydrochloric acid solution with a concentration of 20 wt.%, and ultrasonically treat it at 20±2°C for 120 seconds; filter after the ultrasonic treatment, and wash the copper foil with deionized water until the pH value of the washing solution is 6-7.

[0093] (2) Dilute nitric acid treatment:

[0094] The pretreated copper foil was immersed in a dilute nitric acid solution with a concentration of 3 mol / L and ultrasonically treated at 60±5° C. for 20 seconds.

[0095] (3) First heat treatment

[0096] The copper foil treated with dilute nitric acid was placed in a heating oven with a set temperature of 230°C and a heating time of 30 seconds.

[0097] (4) Electrochemical etching

[0098] Preparation of etching solution: The etching solution is composed of 3 mol / L sodium hydroxide solution and 1 mol / L ammonia water (ie, the concentration ratio is 3:1).

[0099] The copper foil after the first heat treatment is used as the cathode and placed in a U-shaped etching tank filled with the above etching solution. The anode is a stainless steel anode tank 3, and the cathode is fixed on the titanium roller. The temperature of the U-shaped etching tank is controlled at 50°C, the etching time is 25 seconds, and the current density is set to 45mA / cm 2 . Perform electrochemical etching.

[0100] (5) Second heat treatment

[0101] Cleaning: After the electrochemical etching is completed, the porous copper foil is immediately cleaned with ethanol. The cleaning time is 120 seconds, and the pH value of the cleaning solution is measured to be approximately 7.

[0102] Second heat treatment: The cleaned porous copper foil is sent to a heating oven for a second heat treatment. The temperature is set at 250°C and the heating time is 50 seconds to finally obtain a porous copper foil with nano copper oxide on both sides.

[0103] Example 2

[0104] The specific steps and conditions are the same as those in Example 1, except that the molar concentration of dilute nitric acid is 2 mol / L.

[0105] Example 3

[0106] The specific steps and conditions are the same as those in Example 1, except that the molar concentration of dilute nitric acid is 6 mol / L.

[0107] Example 4

[0108] The specific steps and conditions are the same as those in Example 1, except that the dilute nitric acid treatment is performed by ultrasonic treatment at 55±5°C for 35 seconds.

[0109] Example 5

[0110] The specific steps and conditions are the same as those in Example 1, except that the dilute nitric acid treatment is ultrasonically treated at 90±5° C. for 15 seconds.

[0111] Example 6

[0112] The specific steps and conditions are the same as those in Example 1, except that during the first heat treatment, the copper foil treated with dilute nitric acid is placed in a heating oven, the temperature is set to 200° C., and the heating time is 75 seconds.

[0113] Example 7

[0114] The specific steps and conditions are the same as those in Example 1, except that during the first heat treatment, the copper foil treated with dilute nitric acid is placed in a heating oven, the temperature is set to 300° C., and the heating time is 10 seconds.

[0115] Example 8

[0116] The specific steps and conditions are the same as those in Example 1, except that during electrochemical etching, the etching solution consists of 2 mol / L sodium hydroxide solution and 1 mol / L ammonia water (ie, the concentration ratio is 2:1).

[0117] Example 9

[0118] The specific steps and conditions are the same as those in Example 1, except that during electrochemical etching, the temperature of the U-shaped etching tank is controlled at 80°C, the etching time is 15 seconds, and the current density is set to 25 mA / cm 2 . Perform electrochemical etching.

[0119] Example 10

[0120] The specific steps and conditions are the same as those in Example 1, except that during electrochemical etching, the temperature of the U-shaped etching tank is controlled at 40°C, the etching time is 40 seconds, and the current density is set to 65 mA / cm 2 . Perform electrochemical etching.

[0121] Embodiment 11

[0122] The specific steps and conditions are the same as those in Example 1, except that: during the second heat treatment, the cleaned porous copper foil is sent to a heating oven for the second heat treatment. The temperature is set to 210°C and the heating time is 80 seconds; finally, a porous copper foil with nano copper oxide on both sides is obtained.

[0123] Example 12

[0124] The specific steps and conditions are the same as those in Example 1, except that: during the second heat treatment, the cleaned porous copper foil is sent to a heating oven for the second heat treatment. The temperature is set to 400°C and the heating time is 20 seconds; finally, a porous copper foil with nano copper oxide on both sides is obtained.

[0125] Comparative Example 1

[0126] The specific steps and conditions are the same as those in Example 1, except that: first, the pretreated copper foil is heat treated at a temperature of 300°C and a time of 20 seconds; then, a 3 mol / L dilute nitric acid solution is used and ultrasonically treated at 60±5°C for 20 seconds for chemical etching; finally, an etching solution composed of 3 mol / L sodium hydroxide solution and 1 mol / L ammonia water is used for electrochemical etching, wherein the temperature of the U-shaped etching tank is controlled at 50°C, the etching time is 25 seconds, and the current density is set to 45 mA / cm 2 .

[0127] Comparative Example 2

[0128] The specific steps and conditions are the same as those in Example 1, except that the molar concentration of dilute nitric acid is 8 mol / L.

[0129] Comparative Example 3

[0130] The specific steps and conditions are the same as those in Example 1, except that the dilute nitric acid treatment is performed by ultrasonic treatment at 30±5° C. for 15 seconds.

[0131] Comparative Example 4

[0132] The specific steps and conditions are the same as those in Example 1, except that: during the first heat treatment, the copper foil treated with dilute nitric acid is placed in a heating oven, the temperature is set to 100° C., and the heating time is 30 seconds.

[0133] Comparative Example 5

[0134] The specific steps and conditions are the same as those in Example 1, except that during electrochemical etching, the temperature of the U-shaped etching tank is controlled at 200°C, the etching time is 15 seconds, and the current density is set to 25 mA / cm 2 . Perform electrochemical etching.

[0135] Comparative Example 6

[0136] The specific steps and conditions are the same as those in Example 1, except that during electrochemical etching, the etching solution is 8 mol / L sodium hydroxide solution.

[0137] Comparative Example 7

[0138] The specific steps and conditions are the same as those in Example 1, except that the pretreated copper foil is immersed in a sodium hydroxide solution with a concentration of 3 mol / L for alkaline treatment and chemical etching, and is ultrasonically treated at 60±5° C. for 20 seconds.

[0139] Comparative Example 8

[0140] The specific steps and conditions are the same as those in Example 1, except that:

[0141] (2) Sulfuric acid treatment:

[0142] The pretreated copper foil was immersed in a sulfuric acid solution with a concentration of 3 mol / L for chemical etching and ultrasonically treated at 60±5° C. for 20 seconds.

[0143] (3) First heat treatment

[0144] The copper foil treated with sulfuric acid was sent into a heating oven with a set temperature of 500°C and a heating time of 15 seconds.

[0145] Specific test methods and conditions:

[0146] The prepared copper foil was cut into small pieces with a diameter of 12 mm as the positive electrode of the battery, the lithium sheet was used as the negative electrode of the battery, the separator material was PP, the electrolyte formula was 1M LiPF6 EC:DMC=1:1, and the button battery was assembled. The battery test process was to discharge first and then charge, the cut-off voltage range was 0.05-2V, and the charge and discharge current was 0.1mA.

[0147] The test results of Examples 1-12 and Comparative Examples 1-8 are shown in Table 1.

[0148] Table 1

[0149]

[0150]

[0151] Specific test methods and conditions: Prepare water-based graphite negative electrode slurry with a formula of graphite: SP: CMC: SBR = 95: 1: 1.5: 2.5, transfer-coat it on copper foils with different preparation processes, and test the pole piece peeling force after rolling. Assemble 065085 soft-pack batteries with lithium iron phosphate positive electrodes, and test the energy density of the battery at 1C rate discharge, as well as the capacity retention rate after 500 cycles.

[0152] The test results of Examples 1-12 and Comparative Examples 1-8 are shown in Table 2.

[0153] Table 2

[0154]

[0155]

[0156] It can be seen from the data in Table 1 that Example 1-12 successfully prepared a three-dimensional porous copper foil with suitable pore volume, pore size and thickness relative to Comparative Example 1-8; the battery containing the copper foil as the positive electrode has a higher average coulombic efficiency and cycle performance during the charge and discharge cycle test. It can be seen from the data in Table 2 that the negative electrode containing the copper foil also has a higher peeling force and excellent capacity retention rate and energy density during the battery charge and discharge cycle. This result verifies the superiority of the preparation method of the three-dimensional porous copper foil provided by the present invention and the battery using the copper foil in electrochemical performance. By adjusting the preparation parameters of the three-dimensional porous copper foil, the pore structure of the copper foil can be accurately controlled, thereby obtaining a copper foil material with excellent electrochemical properties. This invention not only provides a new idea and method for the preparation of three-dimensional porous copper foil, but the simple and fast preparation method is also conducive to the realization of industrial roll-to-roll production.

[0157] It can be seen from Examples 1-12 and Comparative Example 1 that when the preparation method of the copper foil is changed, and the copper foil is first subjected to heat treatment and then to chemical etching and electrochemical etching, it cannot form a stable three-dimensional porous structure, resulting in the electrochemical performance and pole piece peeling force of the battery of Comparative Example 1 being worse than those of Examples 1-12. In contrast, Examples 1-12 adopt the method of first chemically etching to generate copper nitrate and then subjecting it to simple heat treatment to generate copper oxide, and finally using electrochemical etching, thereby effectively forming a stable three-dimensional porous structure on its surface and inside, thereby obtaining a pore volume, pore diameter and thickness of appropriate size, further improving the electrochemical performance of the battery.

[0158] It can be seen from Examples 1-12 and Comparative Example 2 that when the molar concentration of dilute nitric acid is not within the reasonable range optimized by the present invention, the pore structure of the copper foil prepared therefrom will be affected, and the pore size and pore volume will be difficult to reach a reasonable range, thereby reducing the cycle performance and coulombic efficiency of the prepared battery during the charge and discharge cycle. This may be because the excessively high concentration of dilute nitric acid causes the surface reaction of the copper foil to be too violent, generating a large number of particles and irregular holes, which in turn affects the integrity, uniformity and electrochemical properties of the copper foil, resulting in a low electrode peeling force. In addition, excessively high concentrations may also cause excessive corrosion on the surface of the copper foil, affecting the subsequent preparation of copper foil with a three-dimensional porous structure, and making it impossible to effectively control the thickness of the copper foil, further affecting the performance of the battery.

[0159] It can be seen from Examples 1-12 and Comparative Example 3 that the electrochemical performance and the pore volume, pore diameter and pore thickness of the copper foil of Comparative Example 3 are all inferior to those of Examples 1-12. This may be because when using dilute nitric acid for chemical etching to generate copper nitrate, the chemical etching temperature and time of Comparative Example 3 are not appropriate. When the chemical etching temperature is high and the time is long, the dilute nitric acid corrodes the copper foil to a greater extent, thereby affecting the pore structure of the copper foil and further affecting its electrochemical performance. Therefore, selecting the appropriate chemical etching temperature and time is crucial for preparing a three-dimensional porous copper foil with excellent electrochemical performance.

[0160] It can be seen from Examples 1-12 and Comparative Example 4 that during the first heat treatment, the first heat treatment temperature selected in Comparative Example 4 is lower than that in Examples 1-12; it can also be seen from the data in Tables 1 and 2 that the pore volume and pore size prepared are small, and the thickness is uneven. When used as a negative electrode sheet, the peeling force is also low during the cycle; this may be due to insufficient heat treatment temperature, resulting in the failure of the generated copper oxide layer to completely cover the copper foil surface, making the subsequent electrochemical etching process unable to be fully carried out, thereby affecting the formation of a three-dimensional porous structure; it is not conducive to the uniform deposition of ions, causing the electrode sheet to fall off, and the electrochemical performance of the corresponding battery is poor. Therefore, a reasonable heat treatment temperature is the key to ensuring the integrity and uniformity of the pore structure of the copper foil.

[0161] It can be seen from Examples 1-12 and Comparative Example 5 that when performing electrochemical etching treatment, the electrochemical etching temperature selected in Comparative Example 5 is higher than that in Examples 1-12, resulting in an overly violent electrochemical etching reaction, an uneven distribution of holes on the surface of the copper foil, and some holes are too large, which affects its electrochemical performance. In particular, overly large holes may cause the copper foil to be easily deformed during the battery charge and discharge cycle, thereby affecting the cycle stability and life of the battery. In addition, when the electrochemical etching temperature is high, it is not conducive to regulating the soluble copper oxide to further form suitable pores, and to maintain the structural integrity of the copper foil by maintaining some undissolved copper oxide on the surface of the copper foil. Therefore, selecting appropriate electrochemical etching parameters helps to prepare a three-dimensional porous copper foil with suitable pore volume, pore size, nanofiber skeleton diameter and uniform thickness; avoids uneven deposition of lithium ions and excessive growth of dendrites; uniform deposition of lithium ions is also conducive to enhancing its pole piece peeling force, which is not easy to fall off, thereby improving the electrochemical performance of the battery.

[0162] It can be seen from Examples 1-12 and Comparative Example 6 that the pore volume and pore diameter of Comparative Example 6 are too large, and the number of cycles is lower than that of the embodiment. This is because during electrochemical etching, Comparative Example 6 selects 8 mol / L sodium hydroxide solution as the etching solution, and the concentration of the electrochemical etching solution is too high compared to the embodiment. When the nanoarray is grown on the copper foil surface, the size and distribution of the holes are difficult to control, which in turn affects the pore structure of the copper foil. Excessive pore diameter and pore volume may cause uneven deposition of lithium ions during the charge and discharge process, thereby forming dendrites inside the battery, which not only reduces the cycle stability of the battery, but also may cause safety issues.

[0163] It can be seen from Examples 1-12 and Comparative Example 7 that, compared to Examples 1-12, Comparative Example 7 does not use dilute nitric acid solution for chemical etching to generate copper nitrate, but uses sodium hydroxide solution for alkaline etching; its corresponding pore volume, pore size and pore structure thickness are all worse than those of Examples 1-12; this may be because although alkaline etching generates copper hydroxide, the generation rate and stability of copper hydroxide are not as good as copper nitrate, resulting in the difficulty in accurately controlling the pore structure of the copper foil. In addition, copper hydroxide may decompose or transform during the subsequent heat treatment process, further affecting the pore structure and electrochemical properties of the copper foil, and cannot maintain the stability of the copper foil structure during the reaction process. Therefore, using dilute nitric acid for chemical etching to generate copper nitrate, then converting it into copper oxide through heat treatment, and then electrochemically etching the copper oxide on the surface of the copper foil is more conducive to forming uniform pores inside and on the surface of the copper foil, which is a key step in preparing a three-dimensional porous copper foil with suitable pore size and uniform thickness and excellent electrochemical properties.

[0164] It can be seen from Examples 1-12 and Comparative Example 8 that Comparative Example 8 does not use dilute nitric acid for etching, but uses sulfuric acid for chemical etching. However, the conversion temperature required for copper sulfate to be converted into copper oxide is too high. When the conversion temperature is too high, the microstructure of the copper foil will be damaged, making it rough, thereby affecting the pore structure of the copper foil. Too high a conversion temperature may also cause excessive oxides and impurities to be produced on the surface of the copper foil, which will have an adverse effect on the electrochemical properties of the copper foil. In addition, copper sulfate will also produce harmful sulfur dioxide gas during the decomposition process, which is not conducive to continuous production and use in industry; therefore, the choice of dilute nitric acid as an etchant is reasonable, and it can effectively generate copper nitrate on the surface of the copper foil, and through subsequent heat treatment, it is converted into a stable copper oxide layer, providing a good foundation for electrochemical etching. Thereby ensuring that the copper foil can form a uniform and stable pore structure during the electrochemical etching process. Improve the cycle performance and charge and discharge efficiency of the battery. In addition, the stable pore structure can also effectively alleviate the volume expansion of the battery during the charge and discharge process, and improve the cycle stability of the battery.

[0165] It can be seen from Examples 1, 4, and 5 that the dilute nitric acid chemical etching temperature within the preferred range has a more positive effect on the pore size, pore volume, and thickness of the copper foil, so that the prepared three-dimensional porous copper foil has a more uniform pore distribution and a more optimized pore structure, thereby improving its electrochemical performance.

[0166] It can be seen from Examples 1, 6, and 7 that the first heat treatment temperature and time within the preferred range have a further impact on the formation and distribution of the nano copper oxide layer of the copper foil. Appropriate heat treatment conditions enable the nano copper oxide to be evenly and densely covered on the surface of the copper foil, further improving the conductivity and electrochemical activity of the copper foil.

[0167] It can be seen from Examples 1, 9, and 10 that the electrochemical etching temperature and time within the preferred range have a better effect on the etching effect of the copper foil, and reasonable electrochemical etching conditions can form a more uniform and moderately deep pore structure, further increasing the specific surface area and number of electrochemically active sites of the copper foil. This optimized electrochemical etching process not only enhances the energy storage capacity of the copper foil, but also further improves its cycle stability and electrochemical performance.

[0168] In order to further analyze the structural characteristics of three-dimensional porous copper foils with different parameters, the present invention selected Example 1, Example 2, Example 3, Example 8, and Example 11 for further structural analysis. At the same time, 8 μm original copper foil was selected as a comparison.

[0169] Table 3

[0170] Tensile strength(MPa) Elongation(%) Pore ​​size distribution (μm) Example 1 354.3 7.15 0.05-18 Example 2 352.0 7.77 0.05-20 Example 3 315.6 6.51 5-10 Example 8 358.7 7.40 0.07-19.6 Embodiment 11 289.8 4.33 0.1-20 Original copper foil 363.8 7.85 none

[0171] In addition, the peel strength (gf) of the original copper foil electrode was 20.41 gf under the same conditions and steps as in the embodiment; and the capacity retention rate after 500 cycles was 85%.

[0172] Compared with the original copper foil, we can find that the reasonable fiber bundle diameter, pore volume, pore size distribution, and porous structure thickness have little effect on the tensile strength and elongation of Examples 1, 2, 3, 8, and 11, and at the same time, have a significant improvement on the electrode peeling force and cycle retention rate. The smaller fiber bundle diameter on the surface of Example 11 will reduce the tensile strength and elongation to a certain extent compared with other examples, and at the same time reduce the electrode peeling force and cycle retention rate; Table 3 shows that the smaller pore volume, concentrated pore size distribution, and smaller porous structure thickness have little improvement on the electrode peeling force and cycle retention rate. This is because the larger fiber bundle diameter, wider pore size distribution, and smaller porous structure thickness have less effect on the reduction of the tensile strength and elongation of the copper foil, and the larger pore volume and larger porous structure thickness make the porous structure surface area relatively large, which has a more obvious improvement effect on the cycle, while the smaller fiber bundle diameter and more concentrated pore size distribution have less effect on the improvement of the electrode peeling strength, and the expansion of the negative electrode material after long-term cycling causes the peeling force between the material and the foil to decrease, thereby having a smaller improvement effect on the cycle.

[0173] In order to improve battery performance, we need to have the largest possible fiber bundle diameter and pore volume, the largest possible pore size distribution, and the deepest possible porous structure without significantly reducing the tensile strength and elongation. At the same time, the fiber bundle diameter, pore volume, and pore size distribution will affect each other. The three-dimensional porous copper foil obtained by the specific etching treatment and heat treatment method of the present invention can meet the requirements of obtaining a reasonable fiber bundle diameter, pore volume, pore size distribution, and porous structure thickness while maintaining the tensile strength and elongation to the greatest extent; thereby improving the electrochemical performance and cycle stability during the battery charge and discharge cycle.

[0174] It should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A three-dimensional porous copper foil for battery current collector; characterized in that: The nanofiber skeleton diameter of the three-dimensional porous copper foil is 0.1-3 μm, and the pore volume is 0.005-0.03 cm 3 / cm 2 The average pore size is 1-5μm and the thickness of the porous structure is 1-10μm.

2. The three-dimensional porous copper foil for battery current collector according to claim 1, characterized in that: The pore sizes of the three-dimensional porous copper foil are distributed in the range of 0.05-20 μm.

3. A method for preparing the three-dimensional porous copper foil for battery current collector according to claim 1, characterized in that: The preparation method comprises the following steps: S1: heating the copper foil in a dilute nitric acid solution for chemical etching to obtain a copper foil containing copper nitrate; S2: subjecting the copper foil containing copper nitrate in S1 to a first heat treatment to obtain a copper foil containing copper oxide; S3: electrochemically treating the copper foil containing copper oxide in S2 in an alkaline etching solution to obtain a porous copper foil containing nano copper hydroxide and / or nano copper oxide; S4: subjecting the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3 to a second heat treatment to obtain a porous copper foil containing nano copper oxide.

4. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: The concentration of the dilute nitric acid solution in S1 is selected from 1-6 mol / L; In said S1, the etching temperature is selected from 50-100° C., and the etching time is selected from 15-65 s; Furthermore, the concentration of the dilute nitric acid solution in S1 is preferably 3-5 mol / L; Furthermore, the etching temperature in S1 is preferably from 50 to 80°C.

5. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: In S1, both sides of the copper foil contain copper nitrate; the proportion of copper nitrate is selected from 1% to 5%.

6. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: The temperature of the first heat treatment in S2 is selected from 200-300° C., and the time of the first heat treatment is selected from 5-120 s; the temperature of the second heat treatment in S4 is selected from 200-450° C., and the time of the second heat treatment is selected from 10-120 s; Furthermore, the first heat treatment time in S2 is preferably 20-60s, and the heat treatment temperature is preferably 220-280°C; Furthermore, the temperature of the second heat treatment in S4 is preferably 250-350° C., and the time of the second heat treatment is preferably 20-60 s.

7. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: The etching solution in S3 includes a strong alkali solution and ammonia water; the concentration of the strong alkali solution is selected from 2-5 mol / L; the molar mass ratio of the strong alkali solution to the ammonia water is selected from (2-5): (0.1-1); the strong alkali solution is selected from one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, and barium hydroxide; The step S3 performs electrochemical treatment in an etching tank; the etching tank is preferably a U-shaped etching tank; the U-shaped etching tank comprises a cathode roller (2) and an anode tank (3); the anode tank (3) is also provided with a by-product collection tank (4) on the side opposite to the cathode roller (2); Furthermore, the anode tank (3) is selected from one or more of a stainless steel anode tank, a lead alloy anode tank, and a titanium-based metal oxide coating anode tank; the cathode roller (2) is selected from one or more of a titanium roller, a nickel roller, a stainless steel roller, and a tungsten roller. As some specific examples: the metal oxide coating is selected from one or more of SnO2, PbO2, Sb2O5, RuO2, IrO2, and MnO2.

8. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: In said S3, the electrochemical treatment temperature is selected from 40-110° C., the electrochemical treatment time is selected from 10-65 s, and the electrochemical treatment current density is selected from 10-110 mA / cm 2 ; Furthermore, the electrochemical treatment temperature in S3 is preferably 40-65°C, the electrochemical treatment time is preferably 20-30s, and the current density of the electrochemical treatment is preferably 30-60mA / cm 2 .

9. The method for preparing a three-dimensional porous copper foil for a battery current collector according to claim 3, characterized in that: The copper foil also has a pretreatment step before chemical etching in S1; the pretreatment step is to sequentially subject the copper foil to degreasing with a degreasing liquid, pickling, and water washing; there is also a step S31 between S3 and S4: cleaning the porous copper foil containing nano copper hydroxide and / or nano copper oxide described in S3; removing the etching solution remaining in S3; the heat treatment in S2 and S4 can use one or more equipments of an oven, a vacuum heat treatment furnace, and a muffle furnace; Furthermore, the degreasing liquid is selected from one or more of petroleum ether, acetone, glycerol, ethanol, n-butanol, and isopropanol; Further, the pickling is performed by one or more acid solutions selected from hydrochloric acid, sulfuric acid, acetic acid, and phosphoric acid; the concentration of the acid solution is selected from 20-60wt.%; and the pickling time is selected from 60-200s; Furthermore, in step S31, the pH value of the cleaning solution after cleaning is selected from 6-7; the cleaning time is selected from 60-200s; and the cleaning solvent is selected from one or more of water and ethanol.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte; wherein the positive electrode sheet and / or the negative electrode sheet comprises the three-dimensional porous copper foil according to claim 1.